Pengaruh Variasi Dosis Semangka Kuning (Citrullus Vulgaris Schard)Terhadap Tekanan Darah Lansia Di Panti Wredha Bala Keselamatan Bugangan Semarang - Indah Caturwati; Sufiati Bintanah; Hapsari Sulistya Kusuma (Jurnal Gizi, 2015)
Blood pressure is the amount of force that blood is pressed against the walls of the arteries (arteries) when the heart pumps the blood to all the human body. Blood pressure is one of important indicator in maintaining of healthy body, because the high of blood pressure or hypertension in the long term will lead to stretching the walls of the arteries and lead to rupture of blood vessels . Hypertension is a condition when the blood pressure in the vessels elevated chronically. Hypertension is a global health problem that requires attention because it can cause death in all countries. The purpose of this study was to determine the influence of dosage variation yellow watermelon on the blood pressure in elderly at Panti Wredha Bala Keselamatan Bugangan Semarang.This study is a pre-experimental, with pre-post test. Samples are elderly people living in Panti Wredha Bala Keselamatan Bugangan Semarang with normal blood pressure. The sample size is 15 people. The influence of dosage variation yellow watermelon on the blood pressure were analyzed by T-test.There are 10 persons of sampel are women and 5 persons of sampel are men. The big part of sampel are 60 74 years old, with the youngest is 58 years old and the oldest is 94 years old. There are 8 persons of samples are normal on nutritional status, 6 persons of samples are over wight and 1 person is obesitas. There are the influence of dosage variation yellow watermelon on systolic blood pressure (p value of 0.015). There are also the influence of dosage variation yellow watermelon on the diastolic blood pressure (p value 0.009).There are the influence of the dosage variations of yellow watermelon on blood pressure in elderly at Panti Wredha Bala Keselamatan Bugangan Semarang.Keywords: The Dosage of Yellow Watermelon, The Blood Pressure, The Elderly